2007
DOI: 10.1002/ab.20227
|View full text |Cite
|
Sign up to set email alerts
|

Longer you play, the more hostile you feel: examination of first person shooter video games and aggression during video game play

Abstract: This study investigated the effects of video game play on aggression. Using the General Aggression Model, as applied to video games by Anderson and Bushman, [2002] this study measured physiological arousal, state hostility, and how aggressively participants would respond to three hypothetical scenarios. In addition, this study measured each of these variables multiple times to gauge how aggression would change with increased video game play. Results showed a significant increase from baseline in hostility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 42 publications
(56 reference statements)
3
47
3
3
Order By: Relevance
“…Second, the amount of time between the State Hostility Scale administrations was 15 min, and it is unlikely that participants remembered their responses to all 35 items. Barlett et al [2007] found significant changes in hostility using a similar hostility measure and time frame between scale administrations. However, the results from the aggressive feelings analysis should be interpreted with a certain degree of caution owing to possible practice effects of completing the scale four times.…”
Section: Methodsmentioning
confidence: 73%
“…Second, the amount of time between the State Hostility Scale administrations was 15 min, and it is unlikely that participants remembered their responses to all 35 items. Barlett et al [2007] found significant changes in hostility using a similar hostility measure and time frame between scale administrations. However, the results from the aggressive feelings analysis should be interpreted with a certain degree of caution owing to possible practice effects of completing the scale four times.…”
Section: Methodsmentioning
confidence: 73%
“…First-person shooter games are fast-paced, audiovisually intense, and violent, and game play often results in increased physiologic arousal. 40,41 Given that individuals with ASD are at increased risk for anxiety 42 and sensory reactivity, 43,44 these types of games may be less appealing for many individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…They found support for their hypothesis insofar that participants who played the FPS displayed higher levels of aggression. The authors referred to the General Aggression Model as a possible explanation, suggesting that engaging in violent video games increased aggressive thoughts, which in turn increased aggressive behaviors (Barlett, Harris, & Baldassaro, 2007;Bushman & Anderson, 2002).…”
Section: Pvgu and Aggressionmentioning
confidence: 99%